A journey of self-discovery and survival: A critique of Toni Morrison’s Song of Solomon (1977) - Kumar, Tribhuwan (Research Journal in Advanced Humanities, 2023)
The focus of this study is to examine Toni Morrison's conceptual approach in portraying the main characters of Song of Solomon. Existentialist philosophy and literature largely focus on the inquiry of how humans navigate their existence in a rapidly evolving world. The text explores obligation and freedom as integral aspects of a purposeful existence for individuals. The textual analysis of Song of Solomon formed the basis of the study. Morrison presents Milkman and Pilate, the two main characters in this book, with circumstances that need them to make decisions between different options. This analysis will concentrate on the characters' endeavours to chart their lives and overcome obstacles to underscore the existential concept of the work being examined. This analysis will centre on Morrison's approach and the extent to which she successfully incorporated the social and cultural contexts of the two main characters. The study examines Milkman's inclination to adapt in order to align with his evolving identity, as well as his reluctance to conform to the established norms. In summary, the study thoroughly examines the author's existential perspective and evaluates Aunt Pilate's ability to make autonomous choices and take complete accountability for the outcomes of those choices. The study will centre on the self-perceptions of each character, as well as their perspectives on the community, its norms, and its principles.